2017
DOI: 10.1002/term.2568
|View full text |Cite
|
Sign up to set email alerts
|

A cardiac patch from aligned microvessel and cardiomyocyte patches

Abstract: Cardiac tissue engineering aims to produce replacement tissue patches in the lab to replace or treat infarcted myocardium. However, current patches lack preformed microvascularization and are therefore limited in thickness and force production. In this study, we sought to assess whether a bilayer patch composed of a layer made from human induced pluripotent stem cell-derived cardiomyocytes and a microvessel layer composed of self-assembled human blood outgrowth endothelial cells and pericytes was capable of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 44 publications
2
43
0
1
Order By: Relevance
“…A dense vascular network was obtained, so the authors hypothesized that loading the sheets with an excellent pre-vascularized 3D tissue could be obtained. All of these studies, along with others [ 105 , 106 ], confirmed that a patch containing preformed micro-vessels can be rapidly perfused once implanted, due to its integration with the in vivo host vascular network. This process induces the regrowth and remodeling of the heart tissue, reducing the harmful effects after MI.…”
Section: Epicardial Implanted Cardiac Patchessupporting
confidence: 59%
“…A dense vascular network was obtained, so the authors hypothesized that loading the sheets with an excellent pre-vascularized 3D tissue could be obtained. All of these studies, along with others [ 105 , 106 ], confirmed that a patch containing preformed micro-vessels can be rapidly perfused once implanted, due to its integration with the in vivo host vascular network. This process induces the regrowth and remodeling of the heart tissue, reducing the harmful effects after MI.…”
Section: Epicardial Implanted Cardiac Patchessupporting
confidence: 59%
“…Thus, several micro-devices have been designed and validated, following an ‘organ/lab on chip’ approach [ 228 , 229 ]. The use of such systems offers the advantage to overcome and/or support complex [ 230 , 231 ] co-culture to recreate vascularization and innervation, respectively using artificial perfusion, e.g., micro-channels, and/or electrical stimulation [ 232 , 233 , 234 ]. Further development of these systems could be reached by coupling them with novel bioprinting methods, allowing simulation of complex 3D structure, thus the use of either macro- or micro-bioreactors would offer the chance to perform monitored and standardized in vitro culture protocols leading to the generation of 3D engineered mature tissue grafts.…”
Section: Disease Modellingmentioning
confidence: 99%
“…Moreover, the composition of these cardiac patches should be based on biocompatible materials that can also be biodegraded in a clinically relevant time frame. Recent advancements in the field of material chemistry and microfabrication have allowed the engineering of a variety of cell-laden and acellular cardiac patches, which are based on both synthetic and naturally-derived biomaterials [12,[15][16][17][18][19][20]. However, since electromechanical coupling is essential for the contractile function of the heart, alternative strategies to restore electrical conductivity at the site of MI should also be investigated [21].…”
Section: Introductionmentioning
confidence: 99%